Reductive Heck Reactions of N-Methyl-substituted Tricyclic Imides - Goksu, Gokce; Ocal, Nuket; Kaufmann, Dieter E. (MDPI, 2010)
The palladium-catalyzed hydroarylation of N-methyl-substituted tricyclic imides was studied in order to find a new stereoselective access to a series of new exoaryl( hetaryl)-substituted tricyclic N-methylimides.
Keywords: homogenous catalysis; palladium; C-C coupling; hydroarylation; heterocycles; 1,3-DIPOLAR CYCLOADDITION REACTION; UNSATURATED DICARBOXIMIDES; CYCLIC IMIDES; DERIVATIVES; ANTICANCER; Biochemistry & Molecular Biology; Chemistry